Bi-Furcated Stator Winding Configuration in Three-Phase Induction Generators for Wind Power Generation - P. Meena (IEEE, 2021)
The concerns over the increase in carbon footprints and global climatic changes have given momentum to find ways that reduce the use of fossil fuels to generate electricity. Offshore and onshore windmills for electricity generation are viable options for bulk power generation. A wind generation system has a variable frequency variable voltage supply at the induction generator terminals in response to the changes in the wind velocity and in turn, the speed of the wind turbine. There is a need for an additional power electronic interface to maintain the frequency and voltage at the terminals of the wind generator constant. This paper introduces a novel three-phase Bifurcated Winding Induction Generator (BWIG) comprising a bifurcated set of stator windings. A prototype model has been developed by bifurcating the stator windings of a three-phase induction machine. One part of the winding acts as the excitation winding, and the other half is used as output winding capable of producing three-phase voltages at a constant frequency at all speeds of the prime over. The machine is tested for sub and super synchronous speeds and the characteristics plotted. The flux analysis of the machine is simulated using Ansys Maxwell software. The voltage is controlled by a simple off-on control implemented using a digital controller, TMS320F28335.